Generation of Integration‐Free Induced Neurons Using Graphene Oxide‐Polyethylenimine. Issue 5 (7th November 2016) - Baek, Soonbong; Oh, Jaesur; Song, Juhyun; Choi, Hwan; Yoo, Junsang; Park, Gui‐Yeon; Han, Jin; Chang, Yujung; Park, Hanseul; Kim, Hongwon; Cho, Ssang‐Goo; Kim, Byung‐Soo; et al.
Abstract : Direct conversion of somatic cells into induced neurons (iNs) without inducing pluripotency has great therapeutic potential for treating central nervous system diseases. Reprogramming of somatic cells to iNs requires the introduction of several factors that drive cell‐fate conversion, and viruses are commonly used to deliver these factors into somatic cells. However, novel gene‐delivery systems that do not integrate transgenes into the genome are required to generate iNs for safe human clinical applications. In this study, it is investigated whether graphene oxide‐polyethylenimine (GO‐PEI) complexes are an efficient and safe system for messenger RNA delivery for direct reprogramming of iNs. The GO‐PEI complexes show low cytotoxicity, high delivery efficiency, and directly converted fibroblasts into iNs without integrating factors into the genome. Moreover, in vivo transduction of reprogramming factors into the brain with GO‐PEI complexes facilitates the production of iNs that alleviated Parkinson's disease symptoms in a mouse model. Thus, the GO‐PEI delivery system may be used to safely obtain iNs and could be used to develop direct cell reprogramming‐based therapies for neurodegenerative diseases. Abstract : Oxide polyethylenimine (GO‐PEI) complexes are an efficient and safe system for mRNA delivery for direct reprogramming of integration free iNs. Moreover, in vivo reprogramming with GO‐PEI complexes facilitated the production of iNs that alleviated Parkinson's disease symptoms in a mouse model, suggesting that the GO‐PEI delivery system could be used to develop direct cell reprogramming‐based therapies for neurodegenerative diseases.